PENGARUH IKLIM ETIKA DAN PENGALAMAN KERJA TERHADAP PERSEPSI ETIS AKUNTAN PUBLIK MENGENAI PENGGELAPAN PAJAK - Sunani, Avi (Prodi Akuntansi FEB UNITOMO, 2018)
The purpose of this study is to investigate the effect of ethical climate and work experiences on public accountants’ ethical perception of tax evasion. This study is based on a survey of 84 public accountants in East Java, Indonesia. The direct and moderation effect test was used to examine the effect of ethical climate and work experiences on ethical perceptions of tax evasion. Consistent with the expectations, ethical climate positively affects ethical perceptions of tax evasion. In other words, public accountant perceptions of the extent to which the organization (public accounting firm) supports public interest and social responsibility clearly encourage them to judge tax evasion as more unethical. Besides, work experience positively affects ethical perceptions of tax evasion. This means that experienced auditor are more opposed to tax evasion than are less experienced. This study has documented the moderating influence of work experiences on the association between ethical climate and ethical perceptions of tax evasion.